Hindu Myths - Frank Podgorski (Journal of Dharma, 1976)
In India, mythology often appears at odds with philosophy; myths seem to revere "the flame of life far more than the ocean of release". Hindu Myths (1975) and Asceticism and Eroticism in the Mytho- logy of Siva (1973) represent two efforts by Professor Wendy 0’ Flaherty to illuminate the panorama of Hindu mythology.